2017
DOI: 10.1111/tri.13068
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative immunology: the immunological reaction to biomaterials

Abstract: Regenerative medicine promises to meet two of the most urgent needs of modern organ transplantation, namely immunosuppression-free transplantation and an inexhaustible source of organs. Ideally, bioengineered organs would be manufactured from a patient's own biomaterials-both cells and the supporting scaffolding materials in which cells would be embedded and allowed to mature to eventually regenerate the organ in question. While some groups are focusing on the feasibility of this approach, few are focusing on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 74 publications
1
31
0
1
Order By: Relevance
“…Interestingly enough, natural ECM-based scaffolds obtained from human organs that are being used as supporting scaffolding material for bioengineered tissues, have been reported to contain significant amount of TGF-beta [127][128][129][130] and to be able to induce T-cell apoptosis and promote conversion of naïve CD4 + T cells into CD4 + CD25 + Foxp3 + Treg [118,129]. This observation is consistent with the evidence showing that the ECM possesses strong immunomodulatory properties.…”
Section: Regenerative Immunologysupporting
confidence: 79%
See 1 more Smart Citation
“…Interestingly enough, natural ECM-based scaffolds obtained from human organs that are being used as supporting scaffolding material for bioengineered tissues, have been reported to contain significant amount of TGF-beta [127][128][129][130] and to be able to induce T-cell apoptosis and promote conversion of naïve CD4 + T cells into CD4 + CD25 + Foxp3 + Treg [118,129]. This observation is consistent with the evidence showing that the ECM possesses strong immunomodulatory properties.…”
Section: Regenerative Immunologysupporting
confidence: 79%
“…One of the most critical questions to answer is how the immune system could react against a bioengineered cellular construct and if it would be possible to modulate this response [118]. A bioengineered construct consists of two components, the cellular compartment and the cell-supporting system, namely the ECM.…”
Section: Regenerative Immunologymentioning
confidence: 99%
“…The cellular component of a bioengineered graft may also trigger an acute rejection response because it is well known that both allogeneic pluripotent stem cells and autologous adult cells may still elicit an inflammatory response after manipulation in culture, even when harvested directly from the host. It has also been suggested that the ECM component of scaffolds retains the ability to induce T cell apoptosis and CD4‐positive T cell conversion through innate properties of transforming growth factor β 68–70 . The transition of proinflammatory macrophage phenotype M1 to an M2 phenotype occurring 1–2 weeks after implantation may improve remodelling outcomes by using host tissue remodelling and repair mechanisms 7 .…”
Section: State‐of‐the‐art Regenerative Medicine Technologiesmentioning
confidence: 99%
“…While blood flows through the dialysis membranes, synthetic materials elicit a foreign body reaction characterized by recruitment of neutrophils and monocytes [34,35], which release pro-inflammatory cytokines, namely interleukin 1 (IL-1), interleukin 6 (IL-6), and tumor necrosis factor-α (TNF-α) [36,37]. Therefore, the measurement of activated monocytes provides useful information on dialyzer biocompatibility [38].…”
Section: Cellular Componentsmentioning
confidence: 99%